Faktor - Faktor Determinasi Kualitas Audit (Studi Empiris Pada Kantor Akuntan Publik di Surakarta dan Yogyakarta) - Khasanah, Uswatun; , Dr. Zulfikar, SE, M.Si (2015)
This study entitled "Factors determination of quality audit (empirical studies on public accounting firm in Surakarta and Yogyakarta). This study purpose to analyze the empirical evidence on the influence of work experience, independence, objectivity, integrity, accountability, competence, due professional care, and motivation on quality audit auditor owned public accounting firm Surakarta and Yogyakarta. This research was conducted using survey method with a questionnaire. The study population was all auditors working in Public Accounting Firm (KAP) in Surakarta and Yogyakarta. The sample used as many as 48 respondents in auditor 7 (KAP) Surakarta and Yogyakarta. Data analysis was performed with the validity test and reliability test, classic assumptions test and hypothesis testing with multiple linear regression method. The results showed that the work experience, independence, objectivity, integrity, accountability, due professional care and motivation simultaneously influence audit quality sustainably. In addition, this study proves that the work experience, independence, objectivity, integrity, accountability and motivation partially influence on audit quality but due professional care and competence has no influence on audit quality.